Fast-dissolving solid dispersions for the controlled release of poorly watersoluble drugs - Tran, Phuong H.L.; Lee, Beom Jin; Tran, Thao T.D. (Current Pharmaceutical Design, 2021)
Solid dispersions offer many advantages for oral drug delivery of poorly water-soluble drugs over other systems, including an increase in drug solubility and drug dissolution. An improvement in drug absorption and the higher bioavailability of active pharmaceutical ingredients in the gastrointestinal tract have been reported in various studies. In certain circumstances, a rapid pharmacological effect is required for patients. Fastdissolving solid dispersions provide an ideal formulation in such cases. This report will provide an overview of current studies on fast-dissolving solid dispersions, including not only solid dispersion powders with fast dissolution rates but also specific dose form for the controlled release of poorly water-soluble drugs. Specifically, the applications of fast-dissolving solid dispersions will be described in every specific case. Moreover, pharmaceutical approaches and the utilization of polymers will be summarized. The classification and analysis of fastdissolving solid dispersions could provide insight into strategies and potential applications in future drug delivery developments.
Keywords: Biological Availability; Delayed-Action Preparations; Drug Liberation; Humans; Polymers; Solubility; Controlled release; Fast-dissolving; Oral delivery; Polymers; Poorly water-soluble drugs; Solid dispersion